New insights into the stochastic ray production frontier - Arne Henningsen; Matěj Bělín; Géraldine Henningsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2017)
The stochastic ray production frontier was developed as an alternative to the traditional output distance function to model production processes with multiple inputs and multiple outputs. Its main advantage over the traditional approach is that it can be used when some output quantities of some observations are zero. In this paper, we briefly discuss—and partly refute—a few existing criticisms of the stochastic ray production frontier. Furthermore, we discuss some shortcomings of the stochastic ray production frontier that have not yet been addressed in the literature and that we consider more important than the existing criticisms: taking logarithms of the polar coordinate angles, non-invariance to units of measurement, and ordering of the outputs. We also give some practical advice on how to address the newly raised issues.
Keywords: C13; C51; D22; 330; Stochastic Ray Production Frontier; Distance Function; Multiple Outputs; Primal Approach; Zero Output Quantities